Sexuality in the Posthuman Age - Žižek, Slavoj (Stasis, 2016)
The article begins with a critique of the prevalent interpretation of Platonov’s novels from the 1920s. These novels supposedly present a critical depiction of the Stalinist utopia and its catastrophic consequences. The article argues against such an interpretation by demonstrating that the aforementioned novels do not present a critique of Stalinism but rather a critique of the gnostic-materialist utopia against which late Stalinism reacted in the early 1930s. The article critically confronts various aspects of this utopia of “biocosmism” as the forerunner of today’s technognosis, focusing primarily on its tendency to surpass sexuality as the last stronghold of the bourgeois counterrevolution. This aspect of the critique of the gnostic-materialist utopia is also at work in Platonov’s essay “The Anti-Sexus,” conceived as an advertisement for a masturbatory device. The text discusses this device in the context of the proliferation of gadgets (what Lacan called les lathouses), the “undead” organs which are not mere supplements of the human organism but rather provide the key to the sexuation of human beings as beings of language.